ナンキョクカイ カイテイド ノ ユウキシツ ガンリョウ - 杉村, 行男; スギムラ, ユキオ; 野口, 喜三雄; ノグチ, キミオ; SUGIMURA, Yukio; NOGUCHI, Kimio (国立極地研究所, 1961)
P(論文) The samples investigated were collected off Lutzow-Holm Bay in Antarctica by Dr. T. TORII aboard the "SOYA", research ship of the 2nd Japanese Antarctic Research Expedition (1957-58). The summary of the results is as follows (See the appendix). (1) Organic carbon in dry sediments ranges between 0.15 and 0.30% and organic nitrogen varies from 0.014 to 0.032%. However, the value of org. N/org.C, 0.05-0.17, does not differ from the corresponding values for bottom sediments from other ocean floors. (2) Chlorophyll derivatives which express an amount of pheophytin equivalent are 4-17 p.p.m. The values are less than the correspending values for the sediments off California, 18-46 p.p.m. (3) Marine humus, as calculated from the value of organic carbon and TRASK'S factor (1.72), varies from 0.3 to 0.5%. The values much differs from the corresponding values for the sediments of the northern Pacific, the southern Pacific and the Atlantic oceans, 1-1.5%, 0.4-1.0% and 0.3-1.5%. (4) Carbonate content shows that the value owes mostly to foraminiferal residues, as CaCO_3 varies from 2 to 11%. The number of the observations so far made is greatly limited. Therefore, the tendencies described above are only approaches to further investigation. departmental bulletin paper